Legal Protection of Consumers in Tourism Digital Marketing Strategies in the Digital Economy Era - Harefa, Safaruddin (JELAJAH: Journal of Tourism and Hospitality, 2025)
This research aims to examine the legal protection of consumers in tourism digital marketing strategies in the digital economy era. As the tourism industry develops to utilize digital platforms for marketing, new challenges related to consumer protection arise, such as information transparency, misuse of personal data, and potential fraud in digital transactions. Therefore, it is important to evaluate existing legal protection mechanisms to safeguard consumer rights and ensure the sustainability of the tourism industry. This research uses a qualitative approach with a case study method, collecting data through document analysis, legal literature, and interviews with industry players and consumers. Legal analysis was conducted by comparing the prevailing practices in the tourism sector with legal provisions in Indonesia, such as the Consumer Protection Law (Law No. 8/1999) and the Personal Data Protection Law (Law No. 27/2022). The results show that while there is a strong legal basis for consumer protection, its implementation in the digital tourism sector still faces challenges. Some of the main issues are the lack of information transparency and the potential misuse of personal data. Many consumers feel uninformed about the products they purchase and are concerned about the leakage of their personal data. The conclusion of this study is that Indonesia's tourism sector needs to strengthen consumer protection, especially in terms of information transparency and personal data management. It is recommended that the government and tourism industry players raise awareness and strengthen regulations and supervision of digital marketing practices.